Strengthening and toughening mechanism of (W, Ti, Ta)C based cermet with the addition of c-BN@Al2O3. Issue 22 (15th November 2021) - Yi, Mingdong; Jing, Guiqiang; Li, Depeng; Xiao, Guangchun; Chen, Zhaoqiang; Zhang, Jingjie; Wang, Li; Xu, Chonghai
Abstract: Core-shell particles are considered to be one of the primary strengthening and toughening methods of cermet. In this study, a (W, Ti, Ta)C based cermet was prepared by vacuum hot pressing sintering technology with the addition of c-BN@Al2 O3 (Al2 O3 coated c-BN). Localized high residual stress around the core-shell particles causes the strengthening and toughening mechanism at short distances behind the crack tip, such as crack deflection, secondary cracks, crack branching, and grain pull-out, even at a small volume fraction of 10 vol%. Compared with cermet without Al2 O3 and c-BN, the flexural strength and fracture toughness of the cermet with 10 vol% c-BN@Al2 O3 are increased by 35.62% and 28.45%, reaching 1462 ± 49 MPa and 13.68 ± 0.51 MPa m 1/2, respectively.